Consecutive transcatheter valve-in-valve implantations: the first in the aortic position, the second in the mitral position, in a patient with failing aortic and mitral bioprostheses. (22nd July 2014) - Duncan, Alison; Davies, Simon; Rosendahl, Ulrich; Moat, Neil
Abstract : A 69-year-old man with a failing aortic valve homograft and failing mitral valve xenograft was admitted with an inability to complete full sentences and pulmonary oedema with right ventricular overload. Severe aortic and mitral regurgitation, severe biventricular impairment and pulmonary hypertension were confirmed on transthoracic and transoesophageal echocardiography. An urgent transfemoral valve-in-valve transcatheter valve implantation (TAVI) was performed within the aortic valve homograft with full resolution of aortic regurgitation. Three months later, a semielective trans-apical valve-in-valve procedure was performed in the mitral position, under cardiopulmonary bypass, with full resolution of mitral regurgitation. His exercise tolerance increased from 5 yards to half a mile. This case report summarises a staged double valve-in-valve procedure in a patient who had three previous sternotomies and who had severe heart failure due to failing aortic and mitral bioprostheses. We report two different delivery approaches, using two different transcatheter devices, and describe valve-in-valve techniques, including cardiopulmonary bypass, in the catheter laboratory.